"For Mexico and its Universities": the Puño of the Movimiento Universitario de Renovadora Orientación (MURO) at Universidad Nacional Autónoma de México (UNAM), 1962-1964: "For Mexico and its Universities": the Puño of the Movimiento Universitario de Renovadora Orientación (MURO) at Universidad Nacional Autónoma de México (UNAM), 1962-1964 (Revista de História da UEG (REVHIST), 2021)
This paper analyzes the newspaper Puño published during the first half of the sixties by the Movimiento Universitario de Renovadora Orientación (MURO), an anti-communist Catholic group that operated for more than two decades at the Universidad Nacional Autónoma de México (UNAM). We argue that the content of the publication includes a series of ideas about the university, students and opponents, which distances itself from the physical violence characteristic of the group and it, nuance the radical ideology of its militants as a strategy of approach to the student community.Key words:  UNAM. Right-wing ideology. University. Catholic Anti-Communism. Student movements. Student politicization.